Education on Beyond Use Date (BUD) for Ear and Nasal Drops: Efforts to Increase Patient Awareness in Pharmacies with ENT Doctor Services - Dhafin, Anis Akhwan; Elsa Mahardika Putri; Winartiana; Okki Intan Mawarni; Herman; Maharani Dwi Pritiwi (Journal of Community Engagement in Health, 2025)
The rational and safe use of medication is a critical concern in pharmaceutical practice. A key aspect often overlooked by patients is the Beyond Use Date (BUD), which indicates the time limit for using a medication after its primary packaging has been opened or the preparation compounded. This community service activity aimed to increase public awareness and understanding of BUD, especially regarding non-sterile ENT (ear, nose, and throat) medications. The program was conducted at Sriti Pharmacy in Kediri City on July 22, 2025, involving 26 outpatient participants. The educational method included personal counselling, interactive discussions, and leaflet distribution. Evaluation of the program's impact was performed qualitatively through direct observation and analysis of participant feedback during the sessions. Initial interactions revealed a universal lack of prior knowledge regarding BUD among participants, who frequently confused it with the Expiration Date (ED). Following the intervention, observations indicated a notable increase in participant awareness and engagement. Participants actively asked relevant questions, were able to verbally articulate the distinction between BUD and ED, and expressed a clear understanding of the risks and proper storage practices. These qualitative findings suggest that direct educational interventions in pharmacy settings are a valuable method for improving medication literacy. It is acknowledged that this activity has limitations, primarily the absence of quantitative measurement to formally assess the degree of knowledge improvement and a small sample size at a single location, which limits the generalizability of the findings.